A mixed method, phase 2 clinical evaluation of a novel device to treat postpartum haemorrhage. (April 2023) - Weeks, Andrew D.; Cunningham, Caroline; Taylor, Wendy; Rosala-Hallas, Anna; Watt, Peter; Bryning, Lucy; Ezeofor, Victory; Cregan, Liz; Hayden, Emma; Lambert, Dot; Bedwell, Carol; Lane, Steven; et al.
Abstract: Background: We evaluated the safety, efficacy, and acceptability of a new device designed to facilitate uterine compression in women with postpartum haemorrhage (PPH). Methods: A prospective, phase two clinical device trial with concurrent qualitative study, conducted in a UK consultant obstetric unit. The device was used in addition to standard care in women unresponsive to initial oxytocin therapy. The primary effectiveness outcome was additional blood loss of over 1000mls, whilst safety was assessed through adverse events. Interviews assessed device feasibility and acceptability, and were analysed using framework analysis. Results: We recruited 57 women with clinical PPH after vaginal birth; 67% were primiparous and 47% had undergone operative birth. All but two (96%) had atony as a cause of the haemorrhage; in addition, 30% also had bleeding from lacerations and 11% had retained tissue. After device use, only one woman had additional blood loss over 1000mls, although 3 women (7%) needed a Bakri balloon and 14% received a blood transfusion. All but one clinician felt that the device was easy to use. Clinicians stated that the device assisted management in 85% of cases. All 56 women who responded stated that if they bled in a future birth they would want the device to be used again. There were no serious adverse events related to the device. However, 3 events were judged as 'possibly' being caused by the device − 2 minor vaginal grazes and one postnatal episiotomy infection and breakdown. Lax vaginal tissue complicated the use of the device in three women. In 47 interviews, participants, birth partners, clinician users and attending midwives viewed the device positively. Clinicians found it useful as a way of stopping blood loss and as an aid to diagnose the source of bleeding. Conclusions: The PPH Butterfly may provide a rapid, acceptable and effective treatment for postpartum haemorrhage. Clinical Trial Registration prospective with ISRCTN15452399 11/09/2017 (www.isrctn.com/ISRCTN15452399 ).